1990
DOI: 10.1111/j.1476-5381.1990.tb15839.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of epithelium removal on the actions of cholinomimetic drugs in opened segments and perfused tubular preparations of guinea‐pig trachea

Abstract: Isolated segments of guinea‐pig trachea or perfused tracheal tubes were arranged for the recording of trachealis tension changes in Krebs solution containing indomethacin (2.8 μm). In opened tracheal segments, epithelium removal caused modest (2–3 fold) potentiation of the effects of acetylcholine (ACh) and methacholine (MeCh) but failed to potentiate carbachol (CCh), bethanechol (BeCh), oxotremorine or KCl. Pretreatment with ecothiopate potentiated effects of ACh and MeCh but not of CCh or BeCh. Removal of ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 14 publications
6
34
0
Order By: Relevance
“…However, pathophysiological roles of cholinesterase on airway smooth muscle responsiveness remain unclear. Active staining showed that both acetylcholinesterase and butyrylcholinesterase activities were found in the smooth muscle and ganglia of the rat trachea (Small et al 1990). Chemical oxidant Nchlorosuccinamide (NCS) inhibited both enzyme activities from rat tracheal homogenates in a concentration-dependent fashion .…”
Section: Mucus In the Peripheral Airwaymentioning
confidence: 99%
“…However, pathophysiological roles of cholinesterase on airway smooth muscle responsiveness remain unclear. Active staining showed that both acetylcholinesterase and butyrylcholinesterase activities were found in the smooth muscle and ganglia of the rat trachea (Small et al 1990). Chemical oxidant Nchlorosuccinamide (NCS) inhibited both enzyme activities from rat tracheal homogenates in a concentration-dependent fashion .…”
Section: Mucus In the Peripheral Airwaymentioning
confidence: 99%
“…Although viral respiratory infection decreased epithelium-associated enzymes such as NEP and histamine N-methyltransferase (Dusser et al 1989a; Nakazawa et al, in press), ACNE activity was not influenced by viral respiratory infection (Nakazawa et al in press). Because the airway epithelium does not represent a significant source of ACNE activity (Small et al 1990;Ohrui et al 1991) and AChE only exists in the smooth muscle and ganglia, the location far from the luminal surface of the airway may explain the resistance of this enzyme to noxious stimuli reached from the luminal side. Therefore, pathophysiological significance of AChE may be less in airway diseases.…”
Section: Endopeptidase 2415mentioning
confidence: 99%
“…Studies of cholinesterase activity and of histochemical localization indicate that both ACNE and butyrylcholinesterase (BuChE; EC 3.1.1.8) are present in the smooth muscle and ganglia (Small et al 1990; Ohrui et al 1991). Although both ACNE and BuChE can hydrolyze acetylcholine and are inhibited by physostigmine with different IC50 values (Atack et al 1989), ACNE is a much more efficient enzyme than BuChE.…”
Section: Endopeptidase 2415mentioning
confidence: 99%
“…Small et al (1990) showed that epithelium could modulate smooth muscle activity by both release of epithelium-derived relaxing factors (EpDRF), and by acting as a barrier to drug diffusion in guinea-pig trachea. We cannot evaluate the barrier function because most of the muscle surface in both of our preparations was exposed to the test solution.…”
Section: Maximal Responses and Ec50 Values In Intact Preparationsmentioning
confidence: 99%